Ethnobotany of Medicinal Plants in Leuwiliang (Bogor), Indonesia - Pratami, Mentari Purti; Anggraeni, Anisa; Sujarwo, Prof. Dr. Wawan (Ethnobotany Research and Applications, 2024)
Background: Bogor, a suburban area of Jakarta, harbors a rich diversity of plants traditionally used for medicinal purposes, one of them is Leuwiliang. Furthermore, comprehensive documentation regarding the use of these plants as traditional medicine is lacking. Therefore, this study aims to identify the medicinal plants, their uses, and conservation efforts. Methods: This study involved interviews with users of plant-based medicine. The researchers interviewed thirty respondents from 11 villages. The inquiries encompassed characteristics of both the respondents and the medicinal plants. Additionally, the researchers also conducted exploration, and identification. Results: A total of 101 species belonging to 44 families were identified as potential medicinal plants for treating various ailments prevalent in the Leuwiliang community. The family Zingiberaceae emerged as the most commonly used for medicinal purposes, followed by Asteraceae and other families. Degenerative diseases like diabetes and hypertension were found to be the most prevalent among the Leuwiliang community. Most of the plants used originated from Malesian region, and their conservation status is largely secure, given that most are herbaceous. The community in Leuwiliang practices cultivation of medicinal plants in their home gardens as a conservation effort to prevent these plants from becoming endangered. Conclusions: The abundance of reported medicinal plants underscores the rich traditional knowledge within the Leuwiliang community. However, knowledge regarding the application of these medicinal plants is gradually waning due to the effects of climate change and modernization. Keywords: local wisdom, medicinal plants, plant diversity, traditional knowledge, traditional medicine